3(20x+25)=435

Simple and best practice solution for 3(20x+25)=435 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(20x+25)=435 equation:


Simplifying
3(20x + 25) = 435

Reorder the terms:
3(25 + 20x) = 435
(25 * 3 + 20x * 3) = 435
(75 + 60x) = 435

Solving
75 + 60x = 435

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-75' to each side of the equation.
75 + -75 + 60x = 435 + -75

Combine like terms: 75 + -75 = 0
0 + 60x = 435 + -75
60x = 435 + -75

Combine like terms: 435 + -75 = 360
60x = 360

Divide each side by '60'.
x = 6

Simplifying
x = 6

See similar equations:

| 5=3x^2+6xy | | 8x=0.05 | | At+0.08=11 | | 9n-24n+45=0 | | 8*g=-33 | | 2.00t+(-13.00)=11 | | 28-6x=(14-3x) | | 2[5x+3]=16 | | 7+7m= | | 3F-24= | | (X+8)+(x+5)=1 | | 7.6x-3.5x=65.6 | | (s/7)-11=17 | | b+3(5+20)=4*3+8 | | -18y=6 | | 3p+5=-16 | | 140x+4= | | (3+4)2=38 | | 1+4k+9=26 | | -4(r+2)=-73 | | -13+2*23=11 | | 3+4x+x+3=-2 | | -13+2*22=11 | | 52-(2c+4)=4(c+6)+c | | -13+2*21=11 | | -13+2*20=11 | | b+3(20+30)=3+(2*4) | | 1+4k=26 | | 9-a=2a+13 | | -2r+3r=15-2r | | -13+2*19=11 | | -13+2*17=11 |

Equations solver categories